Clinical characteristics and laboratory parameters in differentiating pediatric Dengue fever and Dengue hemorrhagic fever - A. Juliansen; F. Meliani; C. Budiputri; M. Muljono; R. Heriyanto; S. Chandra; G. Octavius (Infectious Diseases and Tropical Medicine, 2022)
OBJECTIVE: The mortality of dengue hemorrhagic fever (DHF) infection in children is still high. Discriminating dengue fever (DF) and DHF during the early phase is difficult, especially with limited diagnostic tools in peripheral areas. Hence, early identification of significant factors in DHF is important, with rapid disease progression may lead to mortality. This study aims to determine early clinical and laboratory parameters significant in differentiating DF and DHF.